Lithium fluoride and preparation method and application thereof
By controlling the particle size and carbonate content of lithium fluoride, and preparing lithium fluoride by beating and microwave drying, the problems of poor battery electrical performance and difficulty in removing impurities caused by carbonate impurities in existing lithium fluoride products are solved, and efficient impurity removal and improved electrolyte stability are achieved.
Patent Information
- Application Number
- CN202411729269.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Existing lithium fluoride products contain carbonate impurities, resulting in poor quality of electrolyte salts, limited battery electrical performance, and difficult to remove impurities, which are prone to increasing precipitation when applied to electrolytes.
By controlling the particle size and carbonate content of lithium fluoride, specific measures include mixing lithium carbonate with water for beating treatment, then reacting with hydrofluoric acid, and then microwave drying to prepare lithium fluoride with a carbonate content of less than 1000 mg/kg and a particle size meeting specific specifications.
It significantly reduces the impurity content in lithium salt products, improves the stability of the electrolyte, inhibits precipitation and precipitation during storage and application, and improves the electrical and cycling performance of lithium-ion batteries.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to lithium fluoride, in particular to lithium fluoride and a preparation method and application thereof, belonging to the field of lithium ion batteries. Background Art
[0002] As an important lithium-based basic material, lithium fluoride is widely used in many fields. With the growing demand for lithium fluoride in traditional application fields and the emergence of some new application fields, such as optical fiber communication, high-energy chemical power sources, aerospace, etc., the research and preparation of lithium fluoride has become more and more eye-catching.
[0003] It is particularly important that lithium fluoride is an important raw material for electrolyte salts for lithium-ion batteries, such as lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. Its quality has a great impact on the quality of electrolyte products. Therefore, it is crucial to develop a lithium fluoride that is beneficial to improving the quality of electrolyte salts. Summary of the invention
[0004] The invention provides a lithium fluoride having a specific size specification and a lower carbonate impurity content, and the lithium fluoride is helpful for preparing an electrolyte salt capable of improving the electrical performance of a battery.
[0005] The present invention provides lithium fluoride, wherein the mass content of carbonate in the lithium fluoride is less than or equal to 1000 mg / kg;
[0006] The lithium fluoride has a D10 of less than or equal to 10 μm, a D50 of less than or equal to 20 μm, and a bulk density of 0.9-1.2 g / cm 3 .
[0007] The technical solution of the present invention is completed by the inventor based on the following findings:
[0008] When the inventor uses commercially available lithium fluoride as a raw material to prepare battery-grade products, such as hexafluorophosphate or bisfluorosulfonyl imide salts, it is found that the conventional method is used under the conventional operation time, and there is a situation where impurities are difficult to remove, and when this product is applied to the electrolyte, there will be an increase in the amount of sediment in the electrolyte. After analysis, the precipitation may be caused by the impurities brought by hexafluorophosphate or bisfluorosulfonyl imide salts. Initially, it was believed that the impurities were generated during the production process. Therefore, in order to reduce the impurity content, the synthesis process of hexafluorophosphate or bisfluorosulfonyl imide salts was improved, but it was found that the improvement of process parameters had no obvious effect on the improvement of this problem. Then the synthetic raw materials were analyzed again, and it was found that some of the currently commercially available lithium fluoride products contained carbonate impurities, such as lithium carbonate. These carbonate impurities may be brought along because the product is prepared by a technical route using carbonate as a raw material. And it is precisely when raw materials containing carbonate impurities are used to prepare electrolyte products that impurities are difficult to remove and precipitation increases when applied to electrolytes. The inventors analyzed that the reason may be that lithium carbonate can also react with hydrofluoric acid, the raw material for the preparation of lithium hexafluorophosphate, and bisfluorosulfonyl imide, the raw material for the preparation of lithium bisfluorosulfonyl imide. Moreover, since carbonate is an alkaline substance, it is easier to react with the raw materials to generate water than lithium fluoride. Both lithium hexafluorophosphate and lithium bisfluorosulfonyl imide are sensitive to water and will hydrolyze to produce impurities.
[0009] Due to production costs and other commercial factors, the lithium fluoride used cannot avoid the situation where carbonate is used as raw material to prepare it, that is, carbonate must exist in the lithium fluoride product. In this case, the inventor can only try to solve the problem by reducing the carbonate, but found that in the case where carbonate must exist, simply reducing the carbonate content cannot solve the problem well. Later, the inventor accidentally discovered that only by controlling the carbonate content and the size of the lithium fluoride particle size at the same time can the difficulty of impurity removal be solved. When the product is used in the electrolyte, the problem of increased precipitation in the electrolyte will appear. The reason is that when the particle size of the lithium fluoride product is large and the content of alkaline substances is high, when lithium fluoride is used as a raw material to participate in the reaction, the substances on the surface of the lithium fluoride particles and lithium carbonate will react with other reaction raw materials, and lithium carbonate, due to its alkalinity, can react before lithium fluoride to produce impurities. At the same time, due to the large particle size of lithium fluoride, it is not convenient to react quickly, which will cause impurities to adhere to the unreacted lithium fluoride, and further produced products will also adhere to it. The final product will encapsulate the impurities and unreacted lithium fluoride, so that the product prepared with the lithium fluoride will have the problem of difficult removal of impurities and increased precipitation in the electrolyte. Based on this, it is also difficult to avoid the situation where impurities are encapsulated in the product by simply reducing the content of carbonate without controlling the particle size. When the content of carbonate is less than 1000ppm, and the D10 of lithium fluoride is less than or equal to 10μm, the D50 is less than or equal to 20μm, and the bulk density is 0.9-1.2g / cm 3When the lithium fluoride is present in large quantities and its particle size is very small, it will form a competitive reaction relationship with the carbonate and quickly participate in the reaction. The lithium fluoride with a very small particle size is quickly reacted, and the product and impurities will not form a coating relationship. Therefore, even if a small amount of impurities are produced in the end, it is easier to remove because the impurity amount is very small and exists independently in the system.
[0010] The lithium fluoride as described above, wherein the purity of the lithium fluoride is greater than 99.8%, preferably, the purity of the lithium fluoride is greater than 99.9%.
[0011] The lithium fluoride as described above, wherein the mass content of the carbonate is less than or equal to 600 mg / kg; and / or,
[0012] The lithium fluoride has a D10 of less than or equal to 7 μm and a D50 of less than or equal to 15 μm;
[0013] The mass content of the carbonate is greater than or equal to 0.1 mg / kg; and / or,
[0014] The lithium fluoride has a D10 greater than or equal to 1 μm and a D50 greater than or equal to 1 μm.
[0015] The lithium fluoride as described above, wherein the carbonate comprises lithium carbonate.
[0016] The lithium fluoride as described above, wherein the lithium fluoride further includes impurities, wherein: iron ion ≤5ppm, magnesium ion ≤8ppm, calcium ion ≤8ppm, sodium ion ≤10ppm, potassium ion ≤10ppm, aluminum ion ≤5ppm, chloride ion ≤10ppm, sulfate ion ≤10ppm.
[0017] The lithium fluoride as described above, wherein the mass content of water in the lithium fluoride is less than 500 mg / kg.
[0018] The present invention provides a method for preparing lithium fluoride, comprising the following steps:
[0019] 1) mixing lithium carbonate with water and performing slurry treatment to form a lithium carbonate slurry with a mass percentage of 10-30%;
[0020] 2) adding hydrofluoric acid to the lithium carbonate slurry, allowing the system to react at a pH of 3-6 until the pH of the reaction system does not change, thereby obtaining a reactant, and subjecting the reactant to microwave drying to obtain the lithium fluoride;
[0021] Wherein, the reaction temperature is 10-70°C; preferably, the reaction temperature is 30-60°C.
[0022] The lithium fluoride prepared by this method can be used as a raw material for electrolyte salt, which can significantly improve the quality of electrolyte salt and thus improve the electrical performance of the battery. In addition, this method has the advantages of simple process, low equipment requirements and high production efficiency.
[0023] Most of the lithium fluoride currently available in the market is to carbonize lithium carbonate with carbon dioxide to obtain lithium bicarbonate, and then use hydrofluoric acid or ammonium fluoride to fluorinate lithium bicarbonate to obtain lithium fluoride. However, this method has the problems of high residual amount of lithium carbonate. In addition, the inventor found that when the lithium fluoride product particle size is large and the lithium carbonate content is high, when lithium fluoride is used as a raw material to participate in the reaction, the lithium carbonate in the lithium fluoride can react and produce impurities in priority to lithium fluoride due to its alkalinity. At the same time, due to the large particle size of lithium fluoride, it is not convenient to react quickly, which will cause impurities to adhere to unreacted lithium fluoride, and the product produced further will also adhere to it. The final product will be coated with impurities and unreacted lithium fluoride inside, resulting in poor stability and precipitation problems in the electrolyte salt prepared with lithium fluoride as raw material. In order to optimize the purity of lithium fluoride, the preparation method of the present invention creatively pulps lithium carbonate and then reacts it with hydrogen fluoride to obtain crude lithium fluoride, and then uses microwave drying to not only reduce the carbonate content in lithium fluoride, but also adjust the structural size of lithium fluoride, thereby significantly improving the storage stability and application stability of electrolyte salt when lithium fluoride is used as raw material to prepare electrolyte salt.
[0024] The preparation method as described above, wherein the temperature of the pulping treatment is 10-30°C.
[0025] The preparation method as described above, wherein the microwave frequency of the microwave drying is 900-1100 MHz, and the microwave time is 1-2 h.
[0026] The preparation method as described above, wherein the hydrofluoric acid is added to the lithium carbonate slurry by dropwise addition, and the dropwise addition time is 0.5-3h; and / or the mass percentage of the hydrofluoric acid is 30-48%.
[0027] The preparation method as described above, wherein the lithium carbonate is high-purity lithium carbonate, and the impurities in the high-purity lithium carbonate include, in terms of mass percentage, iron ions ≤8ppm, magnesium ions ≤12ppm, calcium ions ≤11ppm, sodium ions ≤14ppm, potassium ions ≤14ppm, aluminum ions ≤7ppm, sulfate ions ≤80ppm, and chloride ions ≤80ppm.
[0028] The preparation method as described above, wherein the pulping process comprises the following steps:
[0029] Divide lithium carbonate with a total mass of m into N parts, where the set of N is denoted by S={1,2,…,i-1,i,…,N};
[0030] Let the mass be m i The i-th part of lithium carbonate and mass M i of water and stirred at a stirring speed V i Performing a pulping process until the viscosity is ≤2 mPa•s to obtain the i-th system;
[0031] The i-th system, with mass m i+1 The i+1th part of lithium carbonate and the mass M i+1 Mix with water and stir at a speed V i+1 Performing a beating process until the viscosity is ≤2 mPa•s to obtain the i+1 system;
[0032] Where 0≤m i / m≤1,1≤m i / m i+1 ≤10, 1≤M i / M i+1 ≤10,0.5≤V i / V i+1 ≤2, i<N, and N≥2;
[0033] The slurrying process is carried out in sequence until all the lithium carbonate and all the water are mixed to form the lithium carbonate slurry.
[0034] The preparation method as described above, wherein the pulping process comprises the following steps:
[0035] Divide lithium carbonate with a total mass of m into three parts, wherein 1 / 2≤m1 / m<1, 0<m2 / m≤1 / 3, 0<m3 / m≤1 / 3;
[0036] The first part of lithium carbonate with a mass of m1 is mixed with water with a mass of M1, and slurried at a stirring speed of V1 until the viscosity is ≤1.6 mPa•s, to obtain a first system;
[0037] The first system, the second part of lithium carbonate with a mass of m2 and water with a mass of M2 are mixed, and slurried at a stirring speed of V2 until the viscosity is ≤1.6 mPa•s to obtain a second system;
[0038] The second system, the third part of lithium carbonate with a mass of m3, is mixed with water with a mass of M3, and slurried at a stirring speed of V3 until the viscosity is ≤1.6 mPa•s, to obtain lithium carbonate slurry;
[0039] Among them, 1≤m1 / m2≤4, 1≤m2 / m3≤3, 1≤M1 / M2≤4, 1≤M2 / M3≤3, 0.5≤V1 / V2≤1, 0.5≤V2 / V3≤1.
[0040] The preparation method as described above, wherein in step 2), after reacting until the pH of the reaction system does not change, further comprises the following steps:
[0041] The pH of the reaction system was adjusted to 7-10.
[0042] The present invention also provides lithium fluoride prepared by the method for preparing lithium fluoride described in any one of the above items, wherein the mass content of carbonate in the lithium fluoride is less than or equal to 1000 mg / kg;
[0043] The lithium fluoride has a D10 of less than or equal to 10 μm, a D50 of less than or equal to 20 μm, and a bulk density of 0.9-1.2 g / cm 3 .
[0044] The present invention provides lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, which are prepared by the above-mentioned lithium fluoride, so the impurity content is low, which helps to improve the electrical performance of the battery. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] At present, the inventors use commercially available lithium fluoride as raw material and prepare battery-grade lithium salt products, such as hexafluorophosphate or bisfluorosulfonyl imide salts, according to the current conventional process. It is found that the impurity content in the lithium salt products is high, and the impurities and lithium salt products are intermixed with each other, making it difficult to achieve efficient impurity removal, and the recovery rate of lithium salt products is low. After such lithium salt products are applied to electrolytes, the electrolyte will also precipitate during storage and application. Based on this, the inventors have partially optimized the process for preparing lithium salt products, but with little success.
[0047] Therefore, the inventors tried to treat commercially available lithium fluoride in order to improve the performance of lithium salt products by improving the quality of lithium fluoride. During the research process, the inventors found that lithium fluoride contains carbonate impurities, such as lithium carbonate, which may be the main cause of quality problems of lithium salt products. In detail, carbonate, as an alkaline compound, is more likely to react with hydrogen fluoride, a raw material for preparing lithium hexafluorophosphate, or bisfluorosulfonyl imide, a raw material for preparing lithium bisfluorosulfonyl imide, to generate water during the preparation of lithium salt products. However, lithium hexafluorophosphate and lithium bisfluorosulfonyl imide have extremely poor water stability and are extremely easy to react with water to generate other impurities, which are then mixed in lithium hexafluorophosphate and lithium bisfluorosulfonyl imide.
[0048] At present, the technical route of using lithium carbonate as a raw material for preparing lithium fluoride is extremely mature, so the feasibility of preparing lithium fluoride by replacing raw materials is low. Therefore, the inventors studied the control of carbonate content in lithium fluoride and achieved preliminary results. However, after the carbonate content was reduced, the quality of the lithium salt product still did not meet expectations.
[0049] Later, the inventors discovered that when the size specifications of lithium fluoride changed at the same time, the quality of the lithium salt product would also change.
[0050] Based on the above concept, the present invention provides a lithium fluoride, wherein the mass content of carbonate in the lithium fluoride is less than 1000 mg / kg; the D10 of the lithium fluoride is less than or equal to 10 μm, the D50 is less than or equal to 20 μm, and the bulk density is 0.9-1.2 g / cm 3 .
[0051] The use of the lithium fluoride of the present invention as a raw material for preparing lithium salt products can significantly reduce the impurity content in the lithium salt products, thereby improving the stability of the electrolyte and inhibiting the precipitation phenomenon during storage and application. The inventor analyzed the reason and believed that the reason is that the size specifications of lithium fluoride also have a relatively important influence on the reaction process. Different size specifications determine the degree of reaction of lithium fluoride, lithium carbonate and hydrofluoric acid or lithium bis(fluorosulfonyl)imide. If the degree of reaction of lithium fluoride with hydrofluoric acid or lithium bis(fluorosulfonyl)imide is lower than that of carbonate, as the reaction proceeds, impurities will be generated in large quantities and lithium fluoride will not be able to react quickly and completely. In the end, impurities and unreacted lithium fluoride will be mixed and wrapped in the lithium salt product, and there will be problems such as impurities being difficult to remove and poor electrolyte stability and easy precipitation. When the size specifications of the lithium fluoride of the present invention meet the requirements that D10 is less than or equal to 10μm, D50 is less than or equal to 20μm, and the bulk density is 0.9-1.2g / cm 3When the carbonate content is less than or equal to 1000 mg / kg, the impurity content in the lithium salt product is significantly reduced and is easier to separate from lithium fluoride. The reason is that when lithium fluoride has this size specification and the carbonate content is low, it will form a competitive reaction relationship with carbonate, and lithium fluoride will quickly participate in the reaction and complete the reaction in a shorter time. Therefore, the impurity content is not only lower, but also the lithium salt product and the impurities will not form a wrapping and inclusion relationship. Therefore, even if a small amount of impurities are generated in the system, it is easier to remove because the impurities are very small and independent of the lithium salt product.
[0052] In a specific embodiment, the purity of lithium fluoride is greater than 99.8%. When the purity of lithium fluoride is within the above range, the content of impurities such as carbonate in lithium fluoride is low, and the impurity content in the lithium salt product prepared from the lithium fluoride is also low, thereby improving the performance of the lithium salt product to a greater extent, and significantly improving the stability of the electrolyte and the performance of the battery. Further, the purity of lithium fluoride is greater than 99.9%.
[0053] The inventors have found that when the particle size of lithium fluoride meets the above requirements, as the mass content of carbonate in lithium fluoride decreases within a certain range, the impurity content in the lithium salt product shows a decreasing trend, especially when the mass percentage of carbonate in lithium fluoride is less than or equal to 600 mg / kg, the storage performance of the lithium salt product prepared by lithium fluoride is even better.
[0054] In addition, when the D10 of lithium fluoride is less than or equal to 7 μm and the D50 is less than or equal to 15 μm, the impurity content in lithium fluoride is also easier to remove, thereby further improving the purity of lithium fluoride. Exemplarily, the D10 of lithium fluoride is 0.5 μm, 1 μm, 2 μm, 3 μm, 3.5 μm, 4 μm, 4.6 μm, 5 μm, 6 μm, 6.1 μm, 7 μm or any range therebetween; the D50 of lithium fluoride is 5 μm, 5.7 μm, 6 μm, 7 μm, 8.5 μm, 10 μm, 11.5 μm, 12 μm, 14 μm, 14.3 μm, 15 μm or any range therebetween.
[0055] Although reducing the mass content of carbonate in lithium fluoride and reducing D10 and D50 in lithium fluoride are beneficial to improving the performance of lithium fluoride, the inventors have found that as the mass content of carbonate in lithium fluoride, as well as D10 and D50, decrease within a certain range, the impurity content in the lithium salt product first shows a decreasing trend, and then remains basically unchanged, and further reducing the mass content of carbonate in lithium fluoride, as well as D10 and D50, will also lead to an increase in the preparation cost of lithium fluoride. Therefore, for economic considerations, the mass content of carbonate is generally greater than or equal to 0.1 mg / kg, the D10 of lithium fluoride is greater than or equal to 1 μm, and the D50 is greater than or equal to 1 μm.
[0056] In one specific embodiment, the carbonate salt in the lithium fluoride comprises lithium carbonate.
[0057] In a specific embodiment, lithium fluoride also contains impurities, and the impurities include, by mass content: iron ions ≤ 5ppm, magnesium ions ≤ 8ppm, calcium ions ≤ 8ppm, sodium ions ≤ 10ppm, potassium ions ≤ 10ppm, aluminum ions ≤ 5ppm, chloride ions ≤ 10ppm, and sulfate ions ≤ 10ppm. When the content of impurity ions in lithium fluoride is within the above range, lithium fluoride has a higher purity, so that the purity of the lithium salt product prepared from the lithium fluoride can be higher, further avoiding the probability of other side reactions in subsequent battery applications that lead to a decrease in battery performance.
[0058] In a specific embodiment, the mass content of water in lithium fluoride is less than 500 mg / kg. When the water content in lithium fluoride is within the above range, the product prepared using the lithium fluoride as a reaction raw material is applied to the electrolyte, which can reduce the water content in the electrolyte and avoid the degradation of the electrochemical performance of the battery caused by the accelerated decomposition of the electrolyte.
[0059] Most of the lithium fluoride currently available on the market is obtained by carbonizing lithium carbonate with carbon dioxide to obtain lithium bicarbonate, and then using hydrofluoric acid or ammonium fluoride to fluorinate the lithium bicarbonate to obtain lithium fluoride. However, this method has the problem of high residual amount of lithium carbonate, resulting in a high content of lithium carbonate in commercially available lithium fluoride, and commercially available lithium fluoride generally adopts the conventional drying method of heating and drying, resulting in a large particle size of commercially available lithium fluoride, which is not conducive to the subsequent application of commercially available lithium fluoride. Therefore, in order to be able to prepare lithium fluoride with the aforementioned carbonate content and size specifications, the present invention provides a method for preparing lithium fluoride, comprising the following steps:
[0060] 1) mixing lithium carbonate with water and performing slurry treatment to form a lithium carbonate slurry with a mass percentage of 10-30%;
[0061] 2) adding hydrofluoric acid to the lithium carbonate slurry, allowing the system to react at a pH of 3-6 until the pH of the reaction system does not change, obtaining a reactant, and subjecting the reactant to microwave drying to obtain lithium fluoride;
[0062] Wherein, the reaction temperature is 10-70°C; preferably, the reaction temperature is 30-60°C.
[0063] Specifically, step 1), lithium carbonate is mixed with water, and then pulped to make the lithium carbonate and water mixed as evenly as possible to obtain lithium carbonate slurry. During the mixing process, the mass ratio of water to lithium carbonate is controlled so that the mass percentage of lithium carbonate in the lithium carbonate slurry is 10-30%. A mass percentage of less than 10% will result in a decrease in yield, while a mass percentage of more than 30% will result in uneven pulping, a high amount of lithium carbonate residue in the product, and the problem of difficult removal of anions.
[0064] The present invention does not limit the specific method used for the beating treatment. For example, stirring treatment, ultrasonic dispersion treatment and the like can be used, and the method can be selected according to actual needs.
[0065] Step 2), under stirring conditions, slowly adding hydrofluoric acid to the lithium carbonate slurry to obtain a reaction system until the pH of the reaction system is 3-6, and then reacting at a reaction temperature of 10-70°C, further 30-60°C, until the pH of the reaction system does not change, to obtain a reaction solution, the reaction solution is subjected to solid-liquid separation and washing treatment to obtain a reactant, and then the reactant is subjected to microwave drying treatment to obtain lithium fluoride.
[0066] The present invention does not limit the specific method of solid-liquid separation, for example, filtration, precipitation and the like can be selected.
[0067] In the washing process of the present invention, water can be used as a washing agent. In order to control the water content of the final lithium fluoride, the mass ratio of the washing agent to the solid phase obtained after solid-liquid separation is generally controlled to be (5-10):1.
[0068] The preparation method of the present invention firstly performs pulping treatment on lithium carbonate and water, which is conducive to the uniform reaction of lithium carbonate and hydrofluoric acid solution, avoids the safety hazard caused by too violent reaction, and can avoid lithium carbonate from being wrapped in the lithium fluoride product, resulting in excessive residual lithium carbonate. In addition, it is ensured that the pH during the reaction is 3-6, which helps to improve the reaction efficiency and allows more lithium carbonate to participate in the reaction to generate lithium fluoride. A pH of less than 3 will result in a decrease in yield, while a pH of greater than 6 will result in an increase in the content of carbonate in the product. During the reaction, hydrofluoric acid is continuously consumed and the pH will continue to increase. Therefore, in order to maintain the pH, hydrofluoric acid needs to be continuously added to the system until the pH no longer occurs, which means that the reaction is completed.
[0069] It is worth mentioning that, because the heat of traditional heating drying is transferred from the outside to the inside, the outer layer of water will evaporate first, resulting in agglomeration and wrapping. Not only is the water content of lithium fluoride high, but it will also lead to a larger particle size of the dried product. Compared with traditional heating, the heat of microwave drying diffuses from the center to the outside, so the water will evaporate more thoroughly from the inside to the outside, and a puffing effect can be produced during the volatilization process, so that the dried product meets the above-mentioned size parameters.
[0070] Therefore, the preparation method of the present invention can prepare carbonate with a mass content of less than 1000 mg / kg, a D10 of less than 10 μm, a D50 of less than 20 μm, and a bulk density of 0.9-1.2 g / cm 3 The lithium fluoride is beneficial to the subsequent application of lithium fluoride, and the method has simple process, low equipment requirements and high production efficiency.
[0071] It can be understood that the temperature of the general beating treatment cannot be too high or too low. If it is lower than 0°C, it is not conducive to the dispersion of lithium carbonate; if the temperature is too high, lithium carbonate may absorb water excessively and increase the water content. Therefore, in order to further ensure the effect of the beating treatment, the above beating treatment is carried out at 10-30°C.
[0072] In a specific embodiment, the microwave frequency of microwave drying is 900-1100 MHz, such as 900 MHz, 920 MHz, 940 MHz, 960 MHz, 980 MHz, 1000 MHz, 1020 MHz, 1040 MHz, 1060 MHz, 1080 MHz or 1100 MHz, and the microwave time is 1-2 h, such as 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, etc. When the microwave frequency and microwave time of microwave drying are within the above ranges, microwave drying can provide sufficient heat to the reactants, so that the water can be rapidly volatilized from the inside to the outside inside the reactants, resulting in a greater puffing effect, so that the particle size of the dried lithium fluoride is smaller, thereby improving the quality of the lithium fluoride to a greater extent.
[0073] In a specific embodiment, hydrofluoric acid is added to the lithium carbonate slurry by dripping, and the dripping time is 0.5-3h, for example, 0.5h, 1h, 1.5h, 2h, 2.5h or 3h. When hydrofluoric acid is slowly dripped into the lithium carbonate slurry, the lithium carbonate can fully react with the hydrofluoric acid solution to ensure that the lithium carbonate is reacted into lithium fluoride, and the reaction process can be avoided to be too violent to cause safety hazards, and the generation of lithium fluoride too fast can be avoided to cause the lithium carbonate to be coated, so that lithium fluoride with high purity and low carbonate content can be obtained. In addition, the dripping time also needs to be determined according to the reaction temperature of step 2). With the addition of hydrofluoric acid, the temperature of the system will increase, so the temperature of the system can be ensured to be between 10-70°C by controlling the dripping time.
[0074] In a specific embodiment, the mass percentage of hydrofluoric acid is 30-48%, for example, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46% or 48%. When the mass percentage of hydrofluoric acid is within the above range, hydrofluoric acid can fully react with lithium carbonate to generate lithium fluoride, and the reaction rate is suitable, and violent reaction can be avoided, so that lithium fluoride with high purity and low carbonate content can be obtained. And under the premise of meeting safety, the water content in the system can be reduced as much as possible, and the generation of impurities in the lithium salt product can be effectively suppressed.
[0075] In a specific embodiment, the lithium carbonate is high-purity lithium carbonate, and the impurities in the high-purity lithium carbonate include, by mass percentage, iron ions ≤8ppm, magnesium ions ≤12ppm, calcium ions ≤11ppm, sodium ions ≤14ppm, potassium ions ≤14ppm, aluminum ions ≤7ppm, sulfate ions ≤80ppm, and chloride ions ≤80ppm. When high-purity lithium carbonate having the above impurity content is used as a raw material for preparing lithium fluoride, the impurity content in the high-purity lithium carbonate is low, so that the impurity content introduced during the preparation of lithium fluoride is low, which is conducive to obtaining high-purity lithium fluoride, and can avoid the occurrence of side reactions of impurities during the preparation of lithium fluoride, resulting in the generation of other by-products, thereby improving the purity of lithium fluoride to a greater extent.
[0076] In one embodiment, the pulping process comprises the following steps:
[0077] Divide lithium carbonate with a total mass of m into N parts, where the set of N is denoted by S={1,2,…,i-1,i,…,N};
[0078] Let the mass be m i The i-th part of lithium carbonate and mass M i of water and stirred at a stirring speed V i Performing a beating process until the viscosity is ≤2 mPa•s to obtain the i-th system;
[0079] The i-th system, with mass m i+1 The i+1th part of lithium carbonate and the mass M i+1 Mix with water and stir at a speed V i+1 Performing a beating process until the viscosity is ≤2 mPa•s to obtain the i+1 system;
[0080] The slurrying treatment is carried out in sequence until all the lithium carbonate and all the water are mixed to form the lithium carbonate slurry, and it is ensured that the mass percentage of lithium carbonate in each system is 10-30%.
[0081] Specifically, the lithium carbonate is divided into N parts (N ≥ 2), and the ratio of lithium carbonate in each part to the total lithium carbonate (m i / m) is in the range of 0-1, and then the i-th part of lithium carbonate (mass m i ) and water (mass M i ) mixed at a stirring speed V i The slurry treatment is performed until the viscosity is ≤2mPa•s to obtain the i-th system; then the i-th system and the i+1-th part of lithium carbonate (mass m i+1 ) and water (mass M i+1 ) mixed at a stirring speed V i+1 Perform beating treatment until the viscosity is ≤2mPa•s to obtain the i+1th system; repeat the above operation until the Nth system is obtained, and control m i / m i+1 The ratio is in the range of 1-10, M i / M i+1 The ratio is in the range of 1-10, V i / V i+1 The ratio is in the range of 0.5-2.
[0082] The present invention can adjust the value of N according to actual conditions. For example, N can be selected from 2, 3, 4, 5 or 6.
[0083] Once the lithium carbonate agglomerates during the beating process, the lithium carbonate inside the agglomerate will be difficult to react with hydrogen fluoride, which will lead to the lithium carbonate outside the agglomerate reacting with hydrogen fluoride to generate lithium fluoride, and the lithium fluoride includes lithium carbonate. Therefore, in order to further reduce the lithium carbonate content in lithium fluoride, the present invention can fully mix the lithium carbonate and water through the beating treatment in batches, avoid the occurrence of agglomeration, and finally realize the preparation of lithium fluoride with high purity and low lithium carbonate content.
[0084] In a specific embodiment, the pulping treatment includes the following steps: dividing lithium carbonate with a total mass of m into three parts, wherein 1 / 2≤m1 / m<1, 0<m2 / m≤1 / 3, and 0<m3 / m≤1 / 3; mixing the first part of lithium carbonate with a mass of m1 with water with a mass of M1, and pulping at a stirring speed V1 until the viscosity is ≤1.6mPa•s to obtain a first system; mixing the first system and the second part of lithium carbonate with a mass of m2 with water with a mass of M2, and The mixture is mixed at a stirring speed of V2 until the viscosity is ≤1.6 mPa•s to obtain a second system; the second system and a third portion of lithium carbonate having a mass of m3 are mixed with water having a mass of M3, and the mixture is mixed at a stirring speed of V3 until the viscosity is ≤1.6 mPa•s to obtain a third system; wherein 1≤m1 / m2≤4, 1≤m2 / m3≤3, 1≤M1 / M2≤4, 1≤M2 / M3≤3, 0.5≤V1 / V2≤1, 0.5≤V2 / V3≤1;
[0085] Specifically, the lithium carbonate is divided into three parts, the mass of the first part is m1, the mass of the second part is m2, and the mass of the third part is m3. Control 1 / 2≤m1 / m<1, 0<m2 / m≤1 / 3, 0<m3 / m≤1 / 3, 1≤m1 / m2≤4, 1≤m2 / m3≤3, then mix the lithium carbonate in the first part with water with a mass of M1, and perform pulping treatment at a stirring rate of V1 until the viscosity is ≤1.6mPa•s to obtain a first system; mix the lithium carbonate in the first system and the second part with water with a mass of M2, and perform pulping treatment at a stirring rate of V2 until the viscosity is ≤1.6mPa•s to obtain a second system; mix the lithium carbonate in the second system and the third part with water with a mass of M3, and perform pulping treatment at a stirring rate of V3 to obtain a third system; control 1≤M1 / M2≤4, 1≤M2 / M3≤3, 0.5≤V1 / V2≤1, 0.5≤V2 / V3≤1.
[0086] The present invention divides the pulping treatment into three steps and controls the parameters of the pulping treatment within the above range, which can make the slurry formed by lithium carbonate more uniform, which is conducive to uniform reaction with the hydrofluoric acid solution and avoids safety hazards. It can also avoid lithium carbonate from being wrapped in the lithium fluoride product to a greater extent, resulting in excessive residual lithium carbonate, thereby further improving the purity of lithium fluoride.
[0087] In a specific embodiment, in step 2), after the reaction is carried out until the pH of the reaction system does not change, the following step is further included: adjusting the pH of the reaction system to 7-10. After the reaction is carried out until the pH does not change, hydrofluoric acid may remain in the reaction system, making the reaction system acidic, and the solubility of lithium fluoride is high under acidic conditions, so the pH of the reaction system is adjusted to 7-10 to reduce the solubility of lithium fluoride, thereby increasing the yield of lithium fluoride and avoiding waste of lithium fluoride.
[0088] The present invention does not limit the raw materials used to adjust the pH of the reaction system to 7-10, and the raw materials can be selected according to actual needs. For example, lithium hydroxide solution can be selected to avoid the introduction of other impurity ions.
[0089] The present invention also provides lithium fluoride prepared by the above method, wherein the mass content of carbonate in the lithium fluoride is less than or equal to 1000 mg / kg; the D10 of the lithium fluoride is less than 10 μm, the D50 is less than or equal to 20 μm, and the bulk density is 0.9-1.2 g / cm 3 .
[0090] Using lithium fluoride as a raw material for preparing lithium salt products can significantly reduce the impurity content in the lithium salt products, thereby improving the stability of the electrolyte, inhibiting precipitation during storage and application, and helping to improve the cycle performance of lithium-ion batteries.
[0091] The present invention also provides lithium hexafluorophosphate, which is prepared by a raw material system including the above lithium fluoride. Specifically, the lithium hexafluorophosphate is prepared by reacting lithium fluoride as a raw material with phosphorus pentafluoride gas under an inert atmosphere.
[0092] In a specific embodiment, lithium fluoride is mixed with anhydrous hydrogen fluoride, and then the mixed solution is reacted with phosphorus pentafluoride at -20 to -5°C to obtain the product.
[0093] In another specific embodiment, lithium fluoride is mixed with an organic solvent, and then the mixed solution is subjected to a reflux reaction with phosphorus pentafluoride. The organic solvent is, for example, ethylene carbonate, diethyl carbonate, dimethyl carbonate, and the like.
[0094] Because lithium fluoride has a special size and low carbonate content, it can quickly participate in the reaction to form lithium hexafluorophosphate, which not only improves the purity of lithium hexafluorophosphate, but also reduces the difficulty of separating lithium hexafluorophosphate from impurities. When lithium hexafluorophosphate is applied to the electrolyte, the storage stability of the electrolyte is higher and the high electrochemical performance of the battery can be guaranteed.
[0095] The present invention also provides a lithium bis(fluorosulfonyl)imide, which is prepared by a raw material system including the above-mentioned lithium fluoride. Specifically, it is prepared in an inert atmosphere with lithium fluoride as a raw material in the absence of a solvent.
[0096] In a specific embodiment, lithium fluoride and bis(fluorosulfonyl)imide are mixed and reacted at 100-140°C to obtain the product.
[0097] Similarly, since lithium fluoride has a special size specification and a low carbonate content, the lithium bis(fluorosulfonyl)imide of the present invention also has higher quality. When the lithium bis(fluorosulfonyl)imide is applied to the electrolyte, the storage stability of the electrolyte is higher and the battery can also be guaranteed to have excellent cycle performance.
[0098] Hereinafter, the present invention will be further described in detail through specific examples.
[0099] Example 1
[0100] The preparation method of lithium fluoride provided in this embodiment comprises the following steps:
[0101] 1) At 30° C., lithium carbonate and water are mixed and slurried to form a lithium carbonate slurry with a mass percentage of 20%. The impurity composition of the lithium carbonate is shown in Table 1A;
[0102] 2) Adding a hydrofluoric acid solution with a mass percentage of 48% to the lithium carbonate slurry for 2 hours, controlling the system to react at a pH of 5 and a temperature of 70°C, and when the pH no longer changes, subjecting the reactant to microwave drying to obtain lithium fluoride; wherein the frequency of the microwave drying treatment is 1000 MHz and the time is 1.5 hours.
[0103] Table 1A
[0104]
[0105] Example 2
[0106] The preparation method of lithium fluoride provided in this embodiment comprises the following steps:
[0107] 1) At 20° C., lithium carbonate and water are mixed and slurried to form a lithium carbonate slurry with a mass percentage of 10%. The impurity composition of the lithium carbonate is shown in Table 1A;
[0108] 2) Adding a hydrofluoric acid solution with a mass percentage of 48% to the lithium carbonate slurry, the addition time is 3 hours, and the system is controlled to react under the conditions of pH 3 and temperature T of 10°C. When the pH no longer changes, the reactant is subjected to microwave drying to obtain lithium fluoride; wherein the frequency of the microwave drying treatment is 900 Hz, and the time is 1.5 hours.
[0109] Example 3
[0110] 1) At 26° C., lithium carbonate and water are mixed and slurried to form a lithium carbonate slurry having a mass percentage of 30%. The impurity composition of the lithium carbonate is shown in Table 1A;
[0111] 2) Adding a hydrofluoric acid solution with a mass percentage of 40% to the lithium carbonate slurry, the addition time is 1 hour, and the system is controlled to react under the conditions of pH 4 and temperature T of 40°C. When the pH no longer changes, the reactant is subjected to microwave drying to obtain lithium fluoride; wherein the frequency of the microwave drying treatment is 1100 Hz and the time is 2 hours.
[0112] Example 4
[0113] 1) At 10° C., lithium carbonate and water are mixed and slurried to form a lithium carbonate slurry having a mass percentage of 30%. The impurity composition of the lithium carbonate is shown in Table 1A;
[0114] 2) Adding a hydrofluoric acid solution with a mass percentage of 48% to the lithium carbonate slurry, the addition time is 0.5h, and the system is controlled to react under the conditions of pH 6 and temperature T of 30°C. When the pH no longer changes, the reactant is subjected to microwave drying to obtain lithium fluoride; wherein the frequency of the microwave drying treatment is 900 Hz and the time is 2h.
[0115] Example 5
[0116] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that the impurity composition of the lithium carbonate in this embodiment is as shown in Table 1B.
[0117] Table 1B
[0118]
[0119] Example 6
[0120] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that the impurity composition of the lithium carbonate in this embodiment is as shown in Table 1C.
[0121] Table 1C
[0122]
[0123] Example 7
[0124] The preparation method of this embodiment is basically the same as that of Example 1, except that the impurity composition of the lithium carbonate in this embodiment is as shown in Table 1D.
[0125] Table 1D
[0126]
[0127] Example 8
[0128] The preparation method of this embodiment is basically the same as that of Example 1, except that the impurity composition of the lithium carbonate in this embodiment is as shown in Table 1E.
[0129] Table 1E
[0130]
[0131] Example 9
[0132] The preparation method of this embodiment is basically the same as that of Example 1, except that the impurity composition of the lithium carbonate in this embodiment is shown in Table 1F.
[0133] Table 1F
[0134]
[0135] Example 10
[0136] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the reaction temperature of this embodiment is 60°C.
[0137] Embodiment 11
[0138] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that the frequency of microwave drying in this embodiment is 700 MHz.
[0139] Example 12
[0140] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that the temperature of the pulping treatment in this embodiment is 5°C.
[0141] Examples 13-14
[0142] The preparation method of lithium fluoride provided in Examples 13-14 is substantially the same as that in Example 1, except that step 1) is a batch beating process, and step 1) comprises the following steps:
[0143] 1) Divide the lithium carbonate of Example 1 with a mass of m into three parts, wherein the mass of the lithium carbonate in the first part is m1, the mass of the lithium carbonate in the second part is M2, and the mass of the lithium carbonate in the third part is m3;
[0144] The first part of lithium carbonate is mixed with water of mass M1, and slurried at a stirring speed V1 until the viscosity is μ1 (mPa•s), thereby obtaining a first system;
[0145] The first system and the second part of lithium carbonate are mixed with water of mass M2, and slurried at a stirring speed V2 until the viscosity is μ2 (mPa•s), thereby obtaining a second system;
[0146] The first system and the third part of lithium carbonate are mixed with water of mass M3, and slurry treatment is performed at a stirring speed V3 until the viscosity is μ3 (mPa•s), thereby obtaining lithium carbonate slurry.
[0147] See Table 2 for specific parameters.
[0148] Table 2
[0149]
[0150] Comparative Example 1
[0151] The preparation method of this comparative example 1 is basically the same as that of Example 1, except that this comparative example does not perform the pulping treatment in step 1).
[0152] Comparative Example 2
[0153] The preparation method of this comparative example 2 is basically the same as that of Example 1, except that the mass percentage of lithium carbonate slurry in the slurrying treatment in step 1) of this comparative example is 40%.
[0154] Comparative Example 3
[0155] The preparation method of this comparative example 3 is basically the same as that of Example 1, except that the reaction temperature of step 2) of this comparative example is 100°C.
[0156] Comparative Example 4
[0157] The preparation method of this comparative example 4 is basically the same as that of Example 1, except that, in step 2) of this comparative example, the reaction is carried out at a pH of 7.
[0158] Comparative Example 5
[0159] The preparation method of this comparative example 5 is substantially the same as that of Example 1, except that the reaction temperature of step 2) of this comparative example is 0°C.
[0160] Test Example 1
[0161] The purity, impurity content, particle size and bulk density of the lithium fluoride of the embodiment and the comparative example were tested, and the results are shown in Table 2A and Table 2B.
[0162] Among them, the lithium carbonate content is detected by acid-base titration; anions such as sulfate ion and chloride ion are detected by ion chromatography; cations such as iron ion, magnesium ion, calcium ion, sodium ion, potassium ion, aluminum ion are detected by ICP-OES inductively coupled plasma emission spectroscopy; the water mass content is detected by drying method; the purity is obtained by the formula: purity = 100% - lithium carbonate content - anion impurity content - cationic impurity content - water mass content; the particle size is detected by a particle size analyzer; the bulk density is detected with reference to GB / T 3603.
[0163] Table 2A
[0164]
[0165] Table 2B
[0166]
[0167] Test Example 2
[0168] The lithium fluoride prepared in Examples 1-4, 10-12 and Comparative Examples 1-5 is used to prepare lithium hexafluorophosphate, comprising the following steps:
[0169] In a nitrogen atmosphere, lithium fluoride and ethylene carbonate solvent were mixed, and the mixed solution was reacted with phosphorus pentafluoride at -20°C for 30 minutes to obtain an ethylene carbonate solution of lithium hexafluorophosphate, which was concentrated to a suitable concentration for standby use. The molar ratio of lithium fluoride to phosphorus pentafluoride was 1:1. The acidity and insoluble matter of the lithium hexafluorophosphate product were tested according to the method of Q / TC 049-2023 lithium hexafluorophosphate concentrate, and the test results are shown in Table 3A below.
[0170] The above-mentioned lithium hexafluorophosphate ethylene carbonate solution is applied to the electrolyte, and the preparation method of the electrolyte includes the following steps: in a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), PC / DEC / PP are mixed evenly in a mass ratio of 20 / 40 / 30 and then mixed with the lithium hexafluorophosphate ethylene carbonate solution, and stirred evenly to form an electrolyte with a mass ratio of EC / PC / DEC / PP of 10 / 20 / 40 / 30 and lithium hexafluorophosphate accounting for 14% of the total mass. The storage stability of the electrolyte at 25°C (0th day, 7th day, 15th day and 30th day) is tested according to the method of Q / TC 060-2024 for electrolytes for lithium ion batteries, and the results are shown in Table 3B.
[0171] Table 3A
[0172]
[0173] Table 3B
[0174]
[0175] Test Example 3
[0176] The lithium fluoride prepared in Examples 1-4, 10-12 and Comparative Examples 1-5 is used to prepare lithium bis(fluorosulfonyl)imide, comprising the following steps:
[0177] Under nitrogen atmosphere, bis(fluorosulfonyl)imide and lithium fluoride were reacted at a molar ratio of 1:1 at 120°C. After 12 hours, the reaction solution was subjected to devolatilization treatment at a vacuum degree of 0.5 kPa, a temperature of 60°C, and a time of 48 hours to obtain lithium bis(fluorosulfonyl)imide. The prepared lithium bis(fluorosulfonyl)imide was tested using the method of Q / TC 054-2023 high-purity lithium bis(fluorosulfonyl)imide, and the results are shown in Table 4A.
[0178] The obtained lithium bis(fluorosulfonyl)imide was applied to an electrolyte. The preparation method of the electrolyte included the following steps: in a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), EC / PC / DEC / PP were mixed in a mass ratio of 10 / 20 / 40 / 30, and then 14% of the total mass of the electrolyte was quickly added to the mixture. The mixture was stirred evenly to obtain a lithium bis(fluorosulfonyl)imide electrolyte. The storage stability of the electrolyte at 25°C (0th day, 7th day, 15th day and 30th day) was tested according to the method of Q / TC 060-2024 for electrolytes for lithium-ion batteries. The results are shown in Table 4B.
[0179] Table 4A
[0180]
[0181] Table 4B
[0182]
[0183] In summary, the lithium fluoride of the present invention, as a raw material, helps to improve the purity of lithium hexafluorophosphate and lithium bisfluorosulfonyl imide, thereby improving the storage stability of the electrolyte including lithium hexafluorophosphate or lithium bisfluorosulfonyl imide.
[0184] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium fluoride, characterized in that: The mass content of carbonate in the lithium fluoride is less than or equal to 1000 mg / kg; The lithium fluoride has a D10 of less than or equal to 10 μm, a D50 of less than or equal to 20 μm, and a bulk density of 0.9-1.2 g / cm 3 .
2. The lithium fluoride according to claim 1, characterized in that The purity of the lithium fluoride is greater than 99.8%, preferably, the purity of the lithium fluoride is greater than 99.9%.
3. The lithium fluoride according to claim 1 or 2, characterized in that: The mass content of the carbonate is less than or equal to 600 mg / kg; and / or, The lithium fluoride has a D10 of less than or equal to 7 μm and a D50 of less than or equal to 15 μm; The mass content of the carbonate is greater than or equal to 0.1 mg / kg; and / or, The lithium fluoride has a D10 greater than or equal to 1 μm and a D50 greater than or equal to 1 μm.
4. The lithium fluoride according to any one of claims 1 to 3, characterized in that The carbonate includes lithium carbonate.
5. The lithium fluoride according to any one of claims 1 to 4, characterized in that The lithium fluoride also includes impurities, including: iron ion ≤5ppm, magnesium ion ≤8ppm, calcium ion ≤8ppm, sodium ion ≤10ppm, potassium ion ≤10ppm, aluminum ion ≤5ppm, chloride ion ≤10ppm, sulfate ion ≤10ppm.
6. The lithium fluoride according to any one of claims 1 to 5, characterized in that The mass content of water in the lithium fluoride is less than 500 mg / kg.
7. A method for preparing lithium fluoride, characterized in that: The following steps are involved: 1) mixing lithium carbonate with water and performing slurry treatment to form a lithium carbonate slurry with a mass percentage of 10-30%; 2) adding hydrofluoric acid to the lithium carbonate slurry, allowing the system to react at a pH of 3-6 until the pH of the reaction system does not change, thereby obtaining a reactant, and subjecting the reactant to microwave drying to obtain the lithium fluoride; Wherein, the reaction temperature is 10-70°C; preferably, the reaction temperature is 30-60°C.
8. The preparation method according to claim 7, characterized in that: The temperature of the pulping treatment is 10-30°C.
9. The method for preparing lithium fluoride according to claim 7 or 8, characterized in that: The microwave frequency of the microwave drying is 900-1100 MHz, and the microwave time is 1-2 h.
10. The method for preparing lithium fluoride according to any one of claims 7 to 9, characterized in that: The hydrofluoric acid is added to the lithium carbonate slurry by dropwise addition, and the dropwise addition time is 0.5-3h; and / or the mass percentage of the hydrofluoric acid is 30-48%.
11. The method for preparing lithium fluoride according to any one of claims 7 to 10, characterized in that: The lithium carbonate is high-purity lithium carbonate, and the impurities in the high-purity lithium carbonate include, by mass percentage, iron ions ≤8ppm, magnesium ions ≤12ppm, calcium ions ≤11ppm, sodium ions ≤14ppm, potassium ions ≤14ppm, aluminum ions ≤7ppm, sulfate ions ≤80ppm, and chloride ions ≤80ppm.
12. The method for preparing lithium fluoride according to any one of claims 7 to 11, characterized in that: The beating process comprises the following steps: Divide lithium carbonate with a total mass of m into N parts, where the set of N is denoted by S={1,2,…,i-1,i,…,N}; Let the mass be m i The i-th part of lithium carbonate and mass M i of water and stirred at a stirring speed V i Performing a beating process until the viscosity is ≤2 mPa•s to obtain the i-th system; The i-th system, with mass m i+1 The i+1th part of lithium carbonate and the mass M i+1 Mix with water and stir at a speed V i+1 Performing a beating process until the viscosity is ≤2 mPa•s to obtain the i+1 system; Where 0≤m i / m≤1,1≤m i / m i+1 ≤10, 1≤M i / M i+1 ≤10,0.5≤V i / V i+1 ≤2, i<N, and N≥2; The slurrying process is carried out in sequence until all the lithium carbonate and all the water are mixed to form the lithium carbonate slurry.
13. The method for preparing lithium fluoride according to claim 12, characterized in that: The beating process comprises the following steps: Divide lithium carbonate with a total mass of m into three parts, wherein 1 / 2≤m1 / m<1, 0<m2 / m≤1 / 3, 0<m3 / m≤1 / 3; The first part of lithium carbonate with a mass of m1 is mixed with water with a mass of M1, and slurried at a stirring speed of V1 until the viscosity is ≤1.6 mPa•s, to obtain a first system; The first system, the second part of lithium carbonate with a mass of m2 and water with a mass of M2 are mixed, and slurried at a stirring speed of V2 until the viscosity is ≤1.6 mPa•s to obtain a second system; The second system, the third part of lithium carbonate with a mass of m3, is mixed with water with a mass of M3, and slurried at a stirring speed of V3 until the viscosity is ≤1.6 mPa•s, to obtain lithium carbonate slurry; Among them, 1≤m1 / m2≤4, 1≤m2 / m3≤3, 1≤M1 / M2≤4, 1≤M2 / M3≤3, 0.5≤V1 / V2≤1, 0.5≤V2 / V3≤1.
14. The method for preparing lithium fluoride according to any one of claims 7 to 13, characterized in that: In step 2), after the reaction is continued until the pH of the reaction system does not change, the following steps are also included: The pH of the reaction system was adjusted to 7-10.
15. Lithium fluoride prepared by the method for preparing lithium fluoride according to any one of claims 7 to 14, characterized in that: The mass content of carbonate in the lithium fluoride is less than or equal to 1000 mg / kg; The lithium fluoride has a D10 of less than or equal to 10 μm, a D50 of less than or equal to 20 μm, and a bulk density of 0.9-1.2 g / cm 3 .
16. A lithium hexafluorophosphate, characterized in that: In an inert gas atmosphere, the lithium fluoride according to any one of claims 1 to 6 or 15 is used as a raw material and reacts with phosphorus pentafluoride gas to obtain the lithium hexafluorophosphate.
17. A lithium bis(fluorosulfonyl)imide, characterized in that: The lithium fluoride according to any one of claims 1 to 6 or 15 is used as a raw material and is prepared under solvent-free conditions.
18. The lithium bis(fluorosulfonyl)imide according to claim 17, characterized in that: In an inert gas atmosphere, the lithium fluoride is reacted with bis(fluorosulfonyl)imide at 100-140° C. to obtain the lithium bis(fluorosulfonyl)imide.
Citation Information
Patent Citations
Production of high-purity lithium fluoride
CN104364198A
Lithium fluoride purification method
CN108751234A
Preparation of nanoscale lithium fluoride and lithium hexafluorophosphate prepared from nanoscale lithium fluoride
CN116239131A
Preparation method of high-purity lithium fluoride
CN116395716A
Purification method of lithium carbonate
CN117699828A
Cited By
Lithium fluoride, and preparation method therefor and use thereof
EP4790023A1
Lithium fluoride, and preparation method therefor and use thereof
WO2026113731A1